The potential of pathogenetic therapy in the treatment of new coronavirus infection COVID-19 - L. A. Shovkun; D. A. Kudlay; E. D. Kampos; N. Yu. Nikolenko; I. F. Shlyk; A. M. Sarychev (Туберкулез и болезни лёгких)
The objective: to increase efcacy of treatment of patients with new coronavirus infection COVID-19 by prescription of Remaxol.Subjects and Methods: 105 patients with confrmed new coronavirus infection COVID-19 with lung damage from 25 to 50% (CT-2) were examined and divided into 2 groups (Main Group and Comparison Group). All patients received standard treatment; patients from Main Group (55 people) additionally received Remaxol intravenously 200.0 ml No. 10 daily, then No. 5 every other day. Treatment efcacy was assessed between the 3rd and 4th week of the study.Results: the patients treated with Remaxol showed more pronounced positive changes of clinical and laboratory symptoms (lower frequency of fever, improved state of health, appetite, decreased dyspnea, cough and wheezing, higher level of SpO2, decreased neutrophilia and blood clotting, ferritin levels, a signifcant increase in activity of superoxide dismutase in erythrocytes and a decrease in myeloperoxidase activity in neutrophils) versus patients receiving standard treatment. The CT lung scan after 3 weeks in patients from Main Group showed the transformation of ground-glass areas into impactions according to the consolidation type in 58.2% (32 people), in 52.2% (29 people) there appeared an organizing pneumonia, a decrease in size of impactions was observed in 54.6% (30 people); in Comparison Group ‒ in 24.0% (12 people), 20% (10 people) and 24% (12 people), respectively, in all three comparisons (p < 0.05).